Perancangan Sistem Monitoring Energi Listrik Menggunakan NodeMCU ESP8266 dan PZEM-004T untuk Pengendalian Penggunaan Daya - Ahmad, Wira; Widiatmoko, Dekki; Kholid, Fajar (Jurnal FORTECH, 2024)
Electricity is one of the essential needs for society today, serving as a primary economicresource. The use of electricity in household sectors reached 50.80% in 2020,contributing to the total electricity consumption in Indonesia each month. To raiseawareness about excessive electricity usage leading to inflated electricity bills, there is aneed for a remote monitoring and control device, based on the Internet of Things (IoT),specifically targeting electronic appliances that consume electricity.Addressing this issue, a research study titled "Design of Electricity Monitoring SystemUsing NodeMCU ESP8266 and PZEM-004T for Controlling Electricity Usage" wasconducted. The energy usage monitoring system is implemented in a terminal socketdevice capable of displaying power consumption through a module. Additionally, thisterminal socket can be connected to the internet, allowing users to view electricity usagedata on the ThingSpeak website. The necessary tools and materials for designing themonitoring and controlling system include a laptop, NodeMCU ESP8266 module,PZEM-004T sensor, relay (Rlay), OLED display, power terminal, plug (Stekker), andjumper cables.Based on testing using the blackbox method, the system has demonstrated effectivemonitoring and control of energy usage. It was observed that the power consumptionstated for an electronic device may differ from the actual power consumed. Thisdifference could be attributed to variations in the stated power consumption informationcompared to the actual power consumption.Keywords: households, NodeMCU ESP8266, PZEM-004T, IoT, electricity monitoring..